Fadzul Rahman Malik: a Contemporary Islamic Thinker - Makmur, Ahmad Diaz; Annisa, Nurul; Muthofia (INSANI: Jurnal Ilmu Agama dan Pendidikan, 2025)
This paper aims to examine the Thinker Fazlur Rahman Malik, a contemporary Islamic intellectual figure, with a focus on his educational background, intellectual experience, as well as his contribution to the modernization of Islamic thought. The method used in this study is a qualitative descriptive analysis of the relevant text sources, by tracing how the context of traditional and modern education forms its perspective. In addition, this study also examines the double movement theory developed by Fazlur Rahman as an interpretative methodology to understand the Qur'an contextually. The findings show that Fazlur Rahman is a contemporary thinker who successfully presents a neo-modernism approach that integrates the traditions of classical Islamic thought and modern critical methods, thus becoming a relevant reference in contemporary Islamic studies today.